Os jornais correio do povo e diário de Pernambuco: a (re) organização política em Pernambuco após a morte de Getúlio Vargas em 1954 - Silva, Daniel Francisco da (2019)
This research aims to analyze the newspapers from the state of Pernambuco Correio do Povo and Diário de Pernambuco after the suicide of Getúlio Vargas for sixty days (08/24/54 to 10/24/54) in order to understand how the press acted during the political reorganization process, in Pernambuco, in the 1954 elections, after the death of Getúlio Vargas. Once the suicide of Getúlio Vargas culminated in a national commotion, which led to the change of the Brazilian political scene, and, in Pernambuco, it was no different. In this way, the Pernambuco press actively contributed to the political recomposition process in Pernambuco, passing through popular manifestations in August 1954, which honored the president; and linking these manifestations to the memory of Vargas, above all, acting in the construction of political subjects that the newspapers would constitute. Therefore, the press acted and played a very important role in the reconstitution of the political frame in Pernambuco during the electoral period. Thus, the press is an object and a source in this study, seen that it is constitutive of the social scene, and that the construction of memories in newspapers is interlaced with journalistic groups’ interests, which have relations with political groups that were in electoral dispute in october 1954. Thereby, the candidacies of João Cleofas - UDN - and Osvaldo Cordeiro de Farias - PSD - for the state government were the core of publications on the surveyed newspapers. Also, the political agreements toward the party coalition for the State and Federal Legislative were evidenced in the newspapers Correio do Povo and Diário de Pernambuco, culminating in constituted memories by these newspapers